A composite coating agent for positive electrode material, a high-nickel single crystal positive electrode material and a battery

By applying a composite coating agent on the surface of the positive electrode material of lithium-ion batteries, the problem of insufficient capacity and cycle stability of the positive electrode material in the prior art is solved, and the effect of reducing residual alkali generation, alleviating surface microcracks and improving safety is achieved.

CN115036493BActive Publication Date: 2025-02-07NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210866765.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-22
Publication Date
2025-02-07
Estimated Expiration
2042-07-22

AI Technical Summary

Technical Problem

The prior art has shortcomings in improving the capacity and cycle stability of the cathode material of lithium-ion batteries, especially in reducing residual alkali generation, alleviating surface microcracks and improving safety.

Method used

Using a composite coating agent, including the first coating agent, the second coating agent and the third coating agent, a uniform coating layer is formed on the surface of the positive electrode material through the combination of different elements, reducing excessive precipitation of Li and alleviating surface microscopicity. Cracked and provide partial energy storage and thermal stability.

Benefits of technology

The capacity and cyclic stability of the cathode material are improved, the residual alkali and gas production rate are reduced, the safety and thermal stability of the material are enhanced, and the overall performance of the material is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003759535560000141
    Figure BDA0003759535560000141
  • Figure BDA0003759535560000151
    Figure BDA0003759535560000151
  • Figure BDA0003759535560000161
    Figure BDA0003759535560000161
Patent Text Reader

Abstract

A composite coating agent for positive electrode materials, a high-nickel single crystal positive electrode material and a battery. The present invention provides a composite coating agent for positive electrode materials, including a first coating agent, a second coating agent and a third coating agent; the first coating agent is a hydroxide, oxide, sulfide, nitrate or carbonate of a first coating element; the second coating agent is a hydroxide, oxide, sulfide, nitrate or carbonate of a second coating element; the third coating agent is a hydroxide, oxide, sulfide, nitrate or carbonate of a third coating element. The composite coating agent in the present invention uses different elements to be composited on the surface of the positive electrode material, which reduces the excessive precipitation of Li in the positive electrode material and thus reduces the formation of residual alkali, alleviates the generation of microcracks on the surface of the positive electrode material, and protects the positive electrode material from direct contact with the electrolyte. The residual lithium of the positive electrode material after coating and the gas production rate of the soft-pack battery will be reduced, thereby improving the safety and stability of the material. The thermal stability of the generated coating element oxide and the protection of the electrolyte improve the material cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery materials, and in particular to a composite coating agent for positive electrode materials, a high-nickel single crystal positive electrode material and a battery. Background Art

[0002] The research and application of positive electrode materials for lithium-ion batteries are very extensive. The prior art CN109713262A discloses a method for preparing a cobalt oxide-coated positive electrode material. It relates to a method for preparing a cobalt oxide-coated positive electrode material, belonging to the technical field of battery positive electrode materials. The problem to be solved is how to achieve high rate performance with low sintering temperature and low coating amount. The method comprises placing a cobalt source and a high nickel positive electrode material in a container, and then stirring and mixing at a rotation speed of ≤700rpm to obtain a corresponding mixed material; in an atmosphere of air or oxygen, the mixed material is subjected to low temperature solid phase sintering treatment at 250℃~550℃ to obtain a corresponding cobalt oxide-coated positive electrode material; the coating amount of cobalt oxide is 0.1wt%~1.0wt% of the mass of the positive electrode material. It can effectively achieve the effect of low cobalt oxide coating, and realize the rate and cycle performance of the material under high pressure conditions. However, the single cobalt source coating in this document only serves as an isolation layer to alleviate the interfacial reaction between the material and the electrolyte, reduce the surface impurities of the material, improve the transmission of lithium ions and reduce polarization; and the coated cobalt after annealing not only generates amorphous cobalt oxide and a small amount of cobalt oxide on the surface of the material, but also generates cobalt tetroxide, a poor conductor, which not only hinders the contact between the charged electrolyte and the positive electrode and hinders the charge transmission, thereby reducing the conductivity of the material, but also causes the unevenness and instability of the coating layer, and there is no solution to the Li / Ni mixing inside the high-nickel ternary positive electrode and the measures to alleviate the generation of internal and external microcracks.

[0003] Prior art CN112194196A discloses a composite coating agent for ultra-high nickel single crystal ternary positive electrode material, its preparation method and application, and discloses a composite coating agent for ultra-high nickel single crystal ternary positive electrode material, its preparation method and application, which belongs to the technical field of lithium-ion power batteries for new energy vehicles. A composite coating agent for ultra-high nickel single crystal ternary positive electrode material, including: at least one of metal and / or non-metal oxides, ammonium salt compounds, and solvents, prepared by at least one process of ball milling, air flow crushing, calcination, wet mixing, and spray drying. The prepared composite coating agent forms a uniform coating layer on the surface of the single crystal material by coating and calcining, and at the same time can reduce the residual alkali level on the surface, and improve the material's cycle performance and safety performance. However, the document adopts a wet process and adds a wet coating liquid. On the one hand, the wet process directly washes away the residual lithium on the surface of the material, and does not improve the Li / Ni mixing and Li transmission channels inside the material. In addition, the over-washing or insufficient washing and uneven washing in the wet process have great damage to the positive electrode material on the surface of the material, resulting in uneven material surface, reduced cycle rate performance and other problems. On the other hand, the use of a wet coating liquid is prone to the coating agent falling off during the charge and discharge process of the positive electrode material, the coating agent cracking, and the electrolyte directly contacts the positive electrode surface, resulting in the positive electrode material particles being more prone to cracks and then ruptures during the charge / discharge cycle, which accelerates the corrosion of the electrolyte to the positive electrode active material, thereby causing a serious capacity drop and poor cycle performance of the lithium-ion battery. In addition, the process is cumbersome and the cost is high, which is not suitable for large-scale industrialization.

[0004] Therefore, it is very necessary to provide a positive electrode material with high capacity and good cycle stability. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a high-nickel single crystal positive electrode material. The positive electrode material provided by the present invention has high capacity and good cycle stability.

[0006] The present invention provides a composite coating agent for positive electrode materials, comprising a first coating agent, a second coating agent and a third coating agent; the first coating agent is a hydroxide, oxide, sulfide, nitrate or carbonate of a first coating element; the second coating agent is a hydroxide, oxide, sulfide, nitrate or carbonate of a second coating element; the third coating agent is a hydroxide, oxide, sulfide, nitrate or carbonate of a third coating element;

[0007] Among them, the first coating element includes one or more of Ni, Mn, Co and B; the second coating element includes one or more of Mg, Al, Nb, W and Mo; the third coating element includes one or more of Ti, Cr, Zr, Y and Sr.

[0008] Preferably, the molar ratio of the first coating element, the second coating element and the third coating element is 1-15:0.1-18:0-12.

[0009] Preferably, the first coating agent is at least one of NiMnCo(OH)2, NiMnCoCO3, Co(OH)2, MnCO3, CoCO3, H3BO3, B(NO3)3, CoOOH or Mn(OH)2.

[0010] Preferably, the second coating agent is at least one of MgO, MgCO3, Mg(OH)2, Al2O3, Al(OH)3, MoO3, Mo(OH)3, WO3, Nb(OH)5 or Nb2O5;

[0011] The third coating agent is at least one of TiO, Cr(OH)2, ZrO2, C2O5Zr, Y2O3 or Sr(OH)2.

[0012] The present invention provides a coating layer, characterized in that it is prepared by the coating agent described in any one of the above technical solutions.

[0013] The present invention provides a high-nickel single crystal positive electrode material, characterized in that it comprises a positive electrode material substrate and a coating layer described in the above technical solution arranged on the surface of the positive electrode material substrate.

[0014] Preferably, the structural formula of the positive electrode material matrix is ​​Li x Ni a M b N c O2, wherein 0.8≤x≤1.05, 0.8≤a≤0.98, b=1-ac, 0≤c<0.2; M is selected from at least one of Mn, Co, Al, Mg or Fe; N is a doping element selected from at least one of Ti, Ta, K, Sb, Na, B, Sc, V, Sn, Y, Zr, Mg, Cr, Nb, W or Mo.

[0015] Preferably, the molar fraction of the coating element in the coating layer to the positive electrode material matrix is ​​0.0001 to 8%.

[0016] Preferably, the coating layer is composed of a lithium-containing coating element oxide and a lithium-free coating element oxide.

[0017] Preferably, in the coating layer, the molar amount of the coating element contained in the lithium-containing coating element oxide accounts for 50% to 89% of the total amount of the coating element.

[0018] Preferably, in the lithium-containing coating element oxide, the molar ratio of the first coating element, the second coating element and the third coating element is 29-100:0-71:0-66.

[0019] The present invention provides a method for preparing a high-nickel single crystal positive electrode material, comprising the following steps:

[0020] A) mixing a ternary precursor and lithium hydroxide monohydrate, adding a dopant, and calcining in the presence of a protective gas to obtain a calcined material;

[0021] B) crushing, removing iron and sieving the calcined material to obtain a positive electrode material matrix;

[0022] C) mixing the cathode material matrix with the coating agent, calcining again in the presence of a protective gas, and then crushing, sieving, and removing iron to obtain a high-nickel single crystal cathode material.

[0023] Preferably, the dopant is selected from at least one of TiO, Ti2O3, Sc2O3, MgO, K2CO3, V2O5, Cr2O3, Sb2O3, Ta2O5, Y2O3, Zr2O3, ZrO2, NaBO2, WO3, MoO3, Nb2O5, etc.;

[0024] Step A) The calcination is specifically carried out at 1-10°C·min -1 The heating rate is 2-4℃·min. The temperature is raised to 190-420℃ and kept at this temperature for 3.5-10.5h. -1 Raise the temperature to 690-920℃, keep warm for 8-11h; then heat at 2-3℃·min -1 Cool down to room temperature;

[0025] Step C) The calcination is specifically carried out by heating the temperature to 500-810° C. at a rate of 3-10° C. / min and keeping the temperature for 9-11 hours.

[0026] The present invention provides a lithium-ion battery, comprising the high-nickel single crystal positive electrode material described in any one of the above technical solutions or the high-nickel single crystal positive electrode material prepared by the preparation method described in any one of the above technical solutions.

[0027] Compared with the prior art, the present invention provides a composite coating agent for a positive electrode material, comprising a first coating agent, a second coating agent and a third coating agent; the first coating agent is a hydroxide, oxide, sulfide, nitrate or carbonate of a first coating element; the second coating agent is a hydroxide, oxide, sulfide, nitrate or carbonate of a second coating element; the third coating agent is a hydroxide, oxide, sulfide, nitrate or carbonate of a third coating element; wherein the first coating element comprises one or more of Ni, Mn, Co and B; the second coating element comprises one or more of Mg, Al, Nb, W and Mo; and the third coating element comprises one or more of Ti, Cr, Zr, Y and Sr. The composite coating agent in the present invention is composited on the surface of the positive electrode material using different elements, which reduces the excessive precipitation of Li in the positive electrode material and thus reduces the formation of residual alkali, alleviates the generation of microcracks on the surface of the positive electrode material, and protects the positive electrode material from direct contact with the electrolyte. Therefore, the residual lithium of the positive electrode material and the gas production rate of the soft-pack battery after being coated with the coating agent of the present invention will be reduced accordingly, thereby improving the safety and stability of the positive electrode material involved in the present invention. In addition, the special lithium-containing coating element oxide contained in the coating layer of the present invention has a partial energy storage effect, thereby improving the capacity and stability of the material to a certain extent. At the same time, the thermal stability brought by the generated coating element oxide and the protection of the electrolyte improve the cycle stability of the material without damaging the material. DETAILED DESCRIPTION

[0028] The present invention provides a composite coating agent for positive electrode materials, a high nickel single crystal positive electrode material and a battery. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It should be pointed out in particular that all similar replacements and modifications are obvious to those skilled in the art, and they all fall within the scope of protection of the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications of this article without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

[0029] The present invention provides a composite coating agent for positive electrode materials, comprising a first coating agent, a second coating agent and a third coating agent; the first coating agent is a hydroxide, oxide, sulfide, nitrate or carbonate of a first coating element; the second coating agent is a hydroxide, oxide, sulfide, nitrate or carbonate of a second coating element; the third coating agent is a hydroxide, oxide, sulfide, nitrate or carbonate of a third coating element;

[0030] Among them, the first coating element includes one or more of Ni, Mn, Co and B; the second coating element includes one or more of Mg, Al, Nb, W and Mo; the third coating element includes one or more of Ti, Cr, Zr, Y and Sr.

[0031] The composite coating agent for positive electrode material provided by the present invention comprises a first coating agent.

[0032] According to the present invention, the first coating agent is a hydroxide, an oxide, a sulfide, a nitrate or a carbonate of a first coating element; the first coating element includes one or more of Ni, Mn, Co and B.

[0033] In some preferred embodiments of the present invention, the first coating agent is at least one of NiMnCo(OH)2, NiMnCoCO3, Co(OH)2, MnCO3, CoCO3, H3BO3, B(NO3)3, CoOOH or Mn(OH)2.

[0034] The composite coating agent for positive electrode material provided by the present invention comprises a second coating agent.

[0035] The second coating agent of the present invention is a hydroxide, oxide, sulfide, nitrate or carbonate of a second coating element; the second coating element includes one or more of Mg, Al, Nb, W and Mo.

[0036] In some preferred embodiments of the present invention, the second coating agent is at least one of MgO, MgCO3, Mg(OH)2, Al2O3, Al(OH)3, MoO3, Mo(OH)3, WO3, Nb(OH)5 or Nb2O5.

[0037] The composite coating agent for positive electrode material provided by the present invention includes a third coating agent.

[0038] The third coating agent of the present invention is a hydroxide, oxide, sulfide, nitrate or carbonate of a third coating element; the third coating element includes one or more of Ti, Cr, Zr, Y and Sr.

[0039] In some preferred embodiments of the present invention, the third coating agent is at least one of CrO3, TiO, Cr(OH)2, ZrO2, C2O5Zr, Y2O3 or Sr(OH)2.

[0040] The composite coating agent of the present invention contains different groups of element types. The combination and proportion of these elements can be used as a coating layer to reduce excessive precipitation of Li and the formation of residual alkali in the positive electrode material, generate Li-containing compounds with energy storage function, and alleviate the generation of microcracks on the surface of the positive electrode material.

[0041] The present invention provides a coating layer prepared by using the coating agent described in any one of the above technical solutions.

[0042] The present invention not only reduces the loss of Li in the material, but also generates a lithium-containing coated element oxide with energy storage function through the reaction of the first coating agent with the excessively precipitated Li in the positive electrode material during the charge and discharge process, thereby preventing the excessively precipitated Li from reacting with H2O and CO2 to generate Li2CO3 under certain conditions, thereby reducing the gas production of the high-nickel ternary positive electrode material battery. On the one hand, the elements in the second coating agent can react with the electrolyte to generate a solid superacid, which can remove impurities on the surface of the positive electrode material and improve the charge transfer in the SEI film on the surface of the positive electrode material and the ion transport in the electrolyte, thereby inhibiting the increase in surface impedance caused by it; on the other hand, the second coating agent has a high thermal stability, which can inhibit the generation of oxygen and enhance the electrolyte, ultimately reducing the loss of electrochemical capacity of the ternary positive electrode material. The elements in the third coating agent will enter the layered structure of the positive electrode material after coating and form chemical bonds with oxygen atoms in the lattice to improve the stability of the material, expand the transmission channel of Li, reduce Li / Ni mixing, and effectively alleviate the occurrence of internal strain and structural degradation.

[0043] The present invention provides a high-nickel single crystal positive electrode material, comprising a positive electrode material substrate and a coating layer according to the above technical solution arranged on the surface of the positive electrode material substrate.

[0044] The structural formula of the cathode material matrix of the present invention is Li x Ni a M b N c O2, wherein 0.8≤x≤1.05, 0.8≤a≤0.98, b=1-ac, 0≤c<0.2; M is selected from at least one of Mn, Co, Al, Mg or Fe; N is a doping element selected from at least one of Ti, Ta, K, Sb, Na, B, Sc, V, Sn, Y, Zr, Mg, Cr, Nb, W or Mo.

[0045] The structural formula of the high nickel single crystal positive electrode material of the present invention is Li x Ni a M b N c O2 / K. K is a coating layer.

[0046] The coating layer is prepared by the coating agent described in any one of the above technical solutions; a part of the coating agent reacts with lithium to obtain a lithium-containing coating element oxide.

[0047] Therefore, the coating layer of the present invention is composed of a lithium-containing coating element oxide and a lithium-free coating element oxide.

[0048] The first cladding element is denoted as K1; the second cladding element is denoted as K2, and the third cladding element is denoted as K3.

[0049] More preferably, K1:K2:K3=1~15:0.1~18:0~12; K1:K2:K3=1~9:0.7~4:0~1.4, K1:K2:K3=5~8:0.8~1.2:0~0.2, K1:K2:K3=2~10:1~10:0~1 , K1:K2:K3=4~8:0.1~0.8:0~0.5, K1:K2:K3=10:1~2:1, K1:K2:K3=6:1~2:0~1, K1:K2:K3=6~10:1~2:0~1, K1:K2:K3=6:1:0, K1:K2: K3=6~8:0.5~2:0~2, K1:K2:K3=6~8:1~4.5:2~3.5, K1:K2:K3=3:2:1, K1:K2:K3=6~8.5:1:0.5~1, K1:K2:K3=6:1~2:0~0.5, K1:K2: K3=0.2~1.2:1~2:0~2, K1:K2:K3=4:1:0.5, K1:K2:K3=8:1.5:0, K1:K2:K3=6:0.7:0.6, K1:K2:K3=7:1:0.9, K1:K2:K3=0.4:1:1.4;

[0050] The molar fraction of the coating element in the coating layer of the present invention to the positive electrode material matrix is ​​preferably 0.0001-8%; more preferably 0.1-8%; most preferably 0.19-8%;

[0051] In some embodiments of the present invention, the molar fraction of the coating element in the coating layer to the positive electrode material matrix is ​​0.016-5.6%; further, it can also be 0.024-0.92%; further, it can also be 0.036-0.78%, further, it can also be 0.052-2.7%, further, it can also be 0.078-6.2%, further, it can also be 4.5-7.6%, further, it can also be 3.8-4.8%, further, it can also be 3.5-3.9%.

[0052] The elements K1, K2 and K3 of the present invention exist in the form of lithium-containing coated element oxides and a small amount of non-lithium-containing coated element oxides, and the lithium-containing coated element oxides are located on the surface of the positive electrode material matrix, which is beneficial to the energy storage performance, and the non-lithium-containing coated element oxides are located outside the lithium-containing coated element oxides, which is beneficial to the gas production performance.

[0053] Furthermore, the coating layer of the present invention is composed of a lithium-containing coating element oxide and a lithium-free coating element oxide.

[0054] The lithium-containing coating element oxide of the present invention is an oxide formed by Li in the positive electrode material and the coating element.

[0055] The molar amount of the coating element contained in the lithium-containing coating element oxide preferably accounts for 50-89% of the total amount of the coating element, more preferably 51-83%; the molar amount of the coating element contained in the non-lithium coating element oxide preferably accounts for 11-50% of the total amount of the coating element.

[0056] In the lithium-containing coating element oxide, the first coating element is recorded as m1; the second coating element is recorded as m2, and the third coating element is recorded as m3.

[0057] Among them, in the lithium-containing coated element oxide, the molar fraction of the coating element contained in the lithium-containing coated element oxide by m1 element is 29 to 100%, the molar fraction of the coating element contained in the lithium-containing coated element oxide by m2 element is 0 to 71%, and the molar fraction of the coating element contained in the lithium-containing coated element oxide by m3 element is 0 to 66%.

[0058] Furthermore, in the lithium-containing coating element oxide, m1:m2:m3=29-100:0-71:0-66; preferably, m1:m2:m3=30-90:2-30:0-15.

[0059] In the present invention, the positive electrode material is more likely to undergo phase change in its near-surface area during contact with the electrolyte, changing from the original layered structure to the spinel phase and the rock salt phase. The Li ion conductivity of these two structures is low, which reduces the transmission of Li ions and increases the polarization of the positive electrode material. In addition, since the coating layer needs to provide a transmission channel for ions and electrons, its unique non-compactness will cause part of the electrolyte to contact the material surface, thereby causing a phase change on the material surface, causing the capacity of the positive electrode material to decay.

[0060] The present invention solves the above problems. The elements doped in the positive electrode material form chemical bonds with oxygen atoms in the lattice to improve the stability of the material, expand the transmission channel of Li, reduce Li / Ni mixing, thereby reducing the formation of NiO rock salt phase on the surface of the positive electrode material, and effectively alleviate the occurrence of internal strain and structural degradation.

[0061] The doped elements in the present invention and the lithium-containing coated element oxides and the non-lithium coated element oxides formed on the surface of the positive electrode material stabilize the internal structure of the material while protecting the surface of the material from electrolyte corrosion and providing a portion of the capacity. Therefore, the doping and coating measures in the present invention generally greatly improve the cycle performance and thermal stability of the single crystal material. At the same time, the residual alkali and gas production levels are lower than those of ordinary single coating modifications, and the overall capacity of the material can be improved to obtain a high-nickel single crystal ternary positive electrode material with good overall performance.

[0062] The present invention provides a method for preparing a high-nickel single crystal positive electrode material, comprising the following steps:

[0063] A) mixing a ternary precursor and lithium hydroxide monohydrate, adding a dopant, and calcining in the presence of a protective gas to obtain a calcined material;

[0064] B) crushing, removing iron and sieving the calcined material to obtain a positive electrode material matrix;

[0065] C) mixing the cathode material matrix with the coating agent, calcining again in the presence of a protective gas, and then crushing, sieving, and removing iron to obtain a high-nickel single crystal cathode material.

[0066] The method for preparing the high-nickel single crystal positive electrode material provided by the present invention firstly mixes a ternary precursor and lithium hydroxide monohydrate.

[0067] The ternary precursor of the present invention is preferably Ni 0.8 Co 0.12 Mn 0.08 (OH)2,Ni 0.8 Co 0.1 Mn 0.1 (OH)2,Ni 0.8 Co 0.15 Al 0.05 (OH)2,Ni 0.82 Co 0.1 Mn 0.08 (OH)2,Ni 0.83 Co 0.12 Mn 0.05 (OH)2,Ni 0.85 Co 0.05 Mn 0.1 (OH)2,Ni 0.85 Co 0.1 Mn 0.05 (OH)2,Ni 0.9 Co 0.05 Mn 0.05 (OH)2,Ni 0.96 Co 0.02 Mn 0.02 (OH)2,Ni 0.98 Co 0.01 Mn 0.01 (OH)2.

[0068] The molar ratio of lithium to the metal in the ternary precursor is 0.8 to 1.05:1. The present invention does not limit the specific mixing method, which is well known to those skilled in the art.

[0069] After mixing, adding a dopant, and calcining in the presence of a protective gas to obtain a calcined material;

[0070] The dopant of the present invention is selected from at least one of TiO, Ti2O3, Sc2O3, MgO, K2CO3, V2O5, Cr2O3, Sb2O3, Ta2O5, Y2O3, Zr2O3, ZrO2, NaBO2, WO3, MoO3, Nb2O5, etc.;

[0071] The addition amount of the dopant of the present invention is preferably 0-0.19wt%, 0.0001-0.15wt%, 0.00015-0.09wt%, 0.0002-0.078wt%, 0.0032-0.054wt%.

[0072] Furthermore, the molar fraction of the doping element in the positive electrode material matrix is ​​preferably 0.28-0.76%; more preferably 0.32-0.64%; and most preferably 0.39-0.64%.

[0073] The present invention does not limit the protective atmosphere, and any protective gas well known to those skilled in the art may be used, including but not limited to nitrogen, helium, argon, etc.

[0074] Specifically, the calcination is carried out at 1 to 10 °C / min. -1 The heating rate is 2-4℃·min. The temperature is raised to 190-420℃ and kept for 3.5-10.5h. -1 Raise the temperature to 690-920℃, keep warm for 8-11h; then heat at 2-3℃·min -1 Cool to room temperature.

[0075] The calcined material is crushed, iron-removed and sieved to obtain a positive electrode material matrix.

[0076] The present invention does not limit the specific operations of crushing, iron removal and screening, which are well known to those skilled in the art.

[0077] The positive electrode material matrix is ​​mixed with a coating agent and calcined again in the presence of a protective gas.

[0078] The ratio of the positive electrode material matrix and the coating agent of the present invention has been clearly described above and will not be repeated here.

[0079] The calcination is specifically carried out by heating the temperature to 500-810°C at a rate of 3-10°C / min and keeping the temperature for 9-11 hours.

[0080] The present invention does not limit the specific operations of crushing, iron removal and screening, which are well known to those skilled in the art.

[0081] The present invention provides a lithium-ion battery, comprising the high-nickel single crystal positive electrode material described in any one of the above technical solutions or the high-nickel single crystal positive electrode material prepared by the preparation method described in any one of the above technical solutions.

[0082] The present invention adopts a dry coating process, which directly washes away the residual lithium on the surface of the material compared to the wet process, but does not improve the Li / Ni mixing inside the material, the Li transmission channel, etc., and the wet process has the unique overwashing or insufficient washing, and the uneven washing has great damage to the positive electrode material on the surface of the material, resulting in uneven material surface, reduced cycle rate performance, etc. The present invention only needs to directly coat the doped positive electrode material, fundamentally solves the generation of residual alkali, does not damage the material, and can obtain a ternary material with good capacity, cycle and rate performance, thereby improving the residual alkali level.

[0083] The coating agent in the present invention is uniformly coated on the surface of the material to form dense small particles, which isolate the electrolyte from contacting the positive electrode material and improve the cycle life of the material. If the mass ratio of the composite coating agent to the high-nickel ternary material in the present invention is less than 0.0001%, the coating agent is insufficient to completely coat the surface of the material, and the electrolyte contacts the positive electrode material, resulting in failure of the coating effect. If the mass ratio of the composite coating agent to the high-nickel ternary material is greater than 8%, the coating layer will be too thick and uneven, resulting in obstruction of lithium ion migration, causing a decrease in rate and cycle behavior.

[0084] The coating layer of the present invention protects the positive electrode material from contact with the electrolyte while providing a portion of capacitance, thereby improving the capacity and stability of the positive electrode material, and improving the residual lithium on the surface of the positive electrode material and the gas production of the final soft-pack battery, thereby improving the safety and stability of the material. In addition, the dry process of the present invention reduces a large amount of energy consumption and equipment process losses during the production process, and therefore has the advantage of being promoted for mass production.

[0085] In order to further illustrate the present invention, a composite coating agent for a positive electrode material, a high-nickel single crystal positive electrode material and a battery provided by the present invention are described in detail below in conjunction with embodiments.

[0086] Embodiment 1:

[0087] The composition of the composite coating agent in this embodiment is H3BO3 and Mo(OH)3, wherein the molar ratio of the first coating element (B), the second coating element (Mo) and the third coating element is 6:1:0, and after being evenly mixed, it is recorded as composite coating agent 1.

[0088] S1. Ni 0.85 Co 0.1 Mn 0.05The (OH)2 ternary precursor was mixed with battery-grade lithium hydroxide monohydrate at a lithium to metal molar ratio of 1.03:1, and a dopant ZrO2 was added at a molar ratio of 0.39%. Then, the mixture was heated in an oxygen atmosphere at 2 °C min -1 The heating rate was 2℃·min -1 Heat to 700℃, keep warm for 10h; load at 3℃·min -1 Cooling to room temperature to obtain a primary calcined material;

[0089] S2. The primary calcined material is coarsely crushed and finely crushed to obtain a crushed material;

[0090] S3. The crushed material is sieved and iron is removed to obtain a primary sintered cathode material matrix;

[0091] S4. The obtained positive electrode material matrix is ​​evenly mixed with the composite coating agent 1, the molar ratio of the coating agent is 0.7%, and then placed in an atmosphere furnace and heated to 650°C at a rate of 5°C / min, kept warm for 10 hours, and then crushed, sieved, and iron removed to obtain a high-nickel single crystal ternary positive electrode material coated with the composite coating agent 1.

[0092] Example 2

[0093] The composition of the composite coating agent in this embodiment is CoCO3 and MgO, wherein the molar ratio of the first coating element (Co), the second coating element (Mg) and the third coating element is 1:1:0, the molar proportion of the coating agent is 1.6%, and the ternary precursor is Ni 0.83 Co 0.12 Mn 0.05 (OH)2, the dopant is TiO, the molar ratio of the dopant is 0.4%, and the remaining steps are the same as those in Example 1, as shown in Table 1.

[0094] Example 3

[0095] The composition of the composite coating agent in this embodiment is CoOOH, Al2O3, CrO3, wherein the molar ratio of the first coating element (Co), the second coating element (Al) and the third coating element (Cr) is 6:0.7:0.6, the molar proportion of the coating agent is 3.71%, and the ternary precursor is Ni 0.82 Co 0.1 Mn 0.08 (OH)2, the dopant is Y2O3, the molar ratio of the dopant is 0.52%, and the remaining steps are the same as those in Example 1, as shown in Table 1.

[0096] Example 4

[0097] The composition of the composite coating agent in this embodiment is Co(OH)2 and MoO3; the molar ratio of the first coating element (Co), the second coating element (Mo) and the third coating element is 5:0.7:0, the molar proportion of the coating agent is 2.66%, and the ternary precursor is Ni 0.85 Co 0.05 Mn 0.1 (OH)2, the dopants are MgO and Ta2O5, the molar ratio of the dopants is 0.46%, and the remaining steps are the same as those in Example 1, as shown in Table 1.

[0098] Example 5

[0099] In this embodiment, the composition of the composite coating agent is Mn(OH)2 and Nb2O5, wherein the molar ratio of the first coating element (Mn), the second coating element (Nb) and the third coating element is 6:1:0, the molar proportion of the coating agent is 4.91%, and the ternary precursor is Ni 0.8 Co 0.1 Mn 0.1 (OH)2, the dopants are MoO3 and NaBO2, the molar ratio of the dopants is 0.5%, and the remaining steps are the same as those in Example 1, as shown in Table 1.

[0100] Example 6

[0101] The composition of the composite coating agent in this embodiment is NiMnCo(OH)2:Nb2O5:ZrO2, wherein the molar ratio of the first coating element (Ni, Mn, Co), the second coating element (Nb) and the third coating element (Zr) is 3:2:1, the molar proportion of the coating agent is 6.76%, and the ternary precursor is Ni 0.8 Co 0.1 Mn 0.1 (OH)2, the dopants are ZrO2 and Cr2O3, the molar ratio of the dopants is 0.57%, and the remaining steps are the same as those in Example 1, as shown in Table 1.

[0102] Example 7

[0103] The composition of the composite coating agent in this embodiment is B(NO3)3, WO3; the molar ratio of the first coating element (B), the second coating element (W) and the third coating element is 6:1:0, the molar proportion of the coating agent is 0.19%, and the ternary precursor is Ni 0.9 Co 0.05 Mn 0.05 (OH)2, the dopants are MoO3, NaBO2, and TiO, and the molar ratio of the dopants is 0.6%. The remaining steps are the same as those in Example 1, as shown in Table 1.

[0104] Example 8

[0105] The composition of the composite coating agent in this embodiment is Mn(OH)2:Al2O3:Sr(OH) 2, The molar ratio of the first coating element (Mn), the second coating element (Al) and the third coating element (Sr) is 7:1:0.9, the molar ratio of the coating agent is 0.86%, and the ternary precursor is Ni 0.96 Co 0.02 Mn 0.02 (OH)2, the dopants are MoO3, Zr2O3, and NaBO2, the molar ratio of the dopants is 0.64%, and the remaining steps are the same as those in Example 1, as shown in Table 1.

[0106] Example 9

[0107] The composition of the composite coating agent in this embodiment is MnCO3:Al2O3:0, wherein the molar ratio of the first coating element (Mn), the second coating element (Al) and the third coating element is 5:1.5:0, the molar proportion of the coating agent is 8.0%, and the ternary precursor is Ni 0.9 Co 0.05 Mn 0.05 (OH)2, the dopant is Nb2O5, the molar ratio of the dopant is 0.62%, and the remaining steps are the same as those in Example 1, as shown in Table 1.

[0108] Example 10

[0109] The composition of the composite coating agent in this embodiment is NiMnCoCO3:WO3:TiO, wherein the molar ratio of the first coating element (NiMnCo), the second coating element (W) and the third coating element (Ti) is 0.4:1:1.4, the molar proportion of the coating agent is 0.8%, and the ternary precursor is Ni 0.8 Co 0.15 Al 0.05 (OH)2, the dopants are Ti2O3, Sc2O3, and MgO, and the molar ratio of the dopants is 0.56%. The remaining steps are the same as those in Example 1, as shown in Table 1.

[0110] Comparative Example 1:

[0111] S1. Ni 0.83 Co 0.12 Mn 0.05 The (OH)2 ternary precursor was mixed with battery-grade lithium hydroxide monohydrate at a lithium to metal molar ratio of 1:1.03, and a dopant TiO was added at a molar ratio of 0.4%. The mixture was heated in an oxygen atmosphere at 2 °C min -1 The heating rate was 2℃·min -1Heat to 700℃, keep warm for 10h; load at 3℃·min -1 Cooling to room temperature to obtain a primary calcined material;

[0112] S2. The primary calcined material is coarsely crushed and finely crushed to obtain a crushed material;

[0113] S3. Screen the crushed material and remove iron to obtain high-nickel single crystal ternary positive electrode material.

[0114] Comparative Example 2

[0115] This comparative example does not contain a coating agent, and the ternary precursor is Ni 0.83 Co 0.12 Mn 0.05 (OH)2, the dopants are Sc2O3 and MgO, the molar ratio of the dopants is 0.57%, and the remaining steps are the same as those in Comparative Example 1, as shown in Table 1.

[0116] Comparative Example 3

[0117] This comparative example does not contain a coating agent, and the ternary precursor is Ni 0.83 Co 0.12 Mn 0.05 (OH)2, the dopants are MoO3, Zr2O3, and NaBO2, the molar ratio of the dopants is 0.64%, and the remaining steps are the same as those in Comparative Example 1, as shown in Table 1.

[0118] Comparative Example 4

[0119] In this comparative example, the coating agent is NiCoMnCO3, the molar proportion of the coating agent is 0.2%, and the ternary precursor is Ni 0.83 Co 0.12 Mn 0.05 (OH)2, without dopant, the remaining steps are the same as those in Example 1, as shown in Table 1.

[0120] Comparative Example 5

[0121] In this comparative example, the coating agent composition is MnCO3 and MgO, wherein the molar ratio of the first coating element (Mn), the second coating element (Mg) and the third coating element is 1:1:0, the molar proportion of the coating agent is 0.4%, and the ternary precursor is Ni 0.83 Co 0.12 Mn 0.05 (OH)2, without dopant, the remaining steps are the same as those in Example 1, as shown in Table 1.

[0122] Comparative Example 6

[0123] In this comparative example, the coating agent composition is NiCoMnCO3, MgO, Sr(OH)2, wherein the molar ratio of the first coating element (NiCoMn), the second coating element (Mg) and the third coating element (Sr) is 1:1:1, the molar proportion of the coating agent is 0.6%, and the ternary precursor is Ni 0.83 Co 0.12 Mn 0.05 (OH)2, without dopant, the remaining steps are the same as those in Example 1, as shown in Table 1.

[0124] Comparative Example 7

[0125] The composition of the composite coating agent in this comparative example is Co(OH)2, WO3, TiO; the molar ratio of the first coating element (Co), the second coating element (W) and the third coating element (Ti) is 0.4:20:1.4, the molar proportion of the coating agent is 6.71%, and the ternary precursor is Ni 0.83 Co 0.12 Mn 0.05 (OH)2, the dopants are Ti2O3, Sc2O3, and MgO, and the molar ratio of the dopants is 0.56%. The remaining steps are the same as those in Example 1, as shown in Table 1.

[0126] Comparative Example 8

[0127] The composition of the composite coating agent in this comparative example is MnCO3, Al2O3, and Y2O3, wherein the molar ratio of the first coating element (Mn), the second coating element (Al), and the third coating element (Y) is 17:1:0.9, the molar proportion of the coating agent is 4.8%, and the ternary precursor is Ni 0.83 Co 0.12 Mn 0.05 (OH)2, the dopants are Sc2O3 and MgO, the molar ratio of the dopants is 0.56%, and the remaining steps are the same as those in Example 1, as shown in Table 1.

[0128] Comparative Example 9

[0129] The composition of the composite coating agent in this comparative example is Zn(OH)2, CaO, Ba(OH)2. The molar ratio of the first coating element (Zn), the second coating element (Ca) and the third coating element (Ba) is 6:1:0, the molar proportion of the coating agent is 1.6%, and the ternary precursor is Ni 0.83 Co 0.12 Mn 0.05 (OH)2, the dopant is MoO3, the molar ratio of the dopant is 0.39%, and the remaining steps are the same as those in Example 1, as shown in Table 1.

[0130] Comparative Example 10

[0131] The composition of the composite coating agent in this comparative example is H3BO3, Mo(OH)3; the molar ratio of the first coating element (B), the second coating element (Mo) and the third coating element is 1:1:0, the molar proportion of the coating agent is 9.9%, and the ternary precursor is Ni 0.83 Co 0.12 Mn 0.05 (OH)2, the dopants are Ti2O3 and Sc2O3, the molar ratio of the dopants is 0.4%, and the remaining steps are the same as those in Example 1, as shown in Table 1.

[0132] Comparative Example 11

[0133] The composition of the composite coating agent in this comparative example is CoCO3 and MgO; the molar ratio of the first coating element (Co), the second coating element (Mg) and the third coating element is 6:0.7:0, the molar proportion of the coating agent is 8.8%, and the ternary precursor is Ni 0.83 Co 0.12 Mn 0.05 (OH)2, the dopants are Zr2O3, MgO, and NaBO2, the molar ratio of the dopants is 0.52%, and the remaining steps are the same as those in Example 1, as shown in Table 1.

[0134] Comparative Example 12

[0135] The composition of the composite coating agent in this comparative example is CoOOH, Al2O3, CrO3; the molar ratio of the first coating element (Co), the second coating element (Al) and the third coating element (Cr) is 5:0.7:0.6, the molar proportion of the coating agent is 2.66%, and the ternary precursor is Ni 0.83 Co 0.12 Mn 0.05 (OH)2, the dopant is MoO3, the molar ratio of the dopant is 0.46%, and the remaining steps are the same as those in Example 1, as shown in Table 1.

[0136] Comparative Example 13

[0137] The composition of the composite coating agent in this comparative example is Mn(OH)2 and Nb2O5; the molar ratio of the first coating element (Mn), the second coating element (Nb) and the third coating element is 3:2:0, the molar proportion of the coating agent is 6.76%, and the ternary precursor is Ni 0.83 Co 0.12 Mn 0.05 (OH)2, the dopants are Zr2O3, MgO, and NaBO2, the molar ratio of the dopants is 0.57%, and the remaining steps are the same as those in Example 1, as shown in Table 1.

[0138] Comparative Example 14

[0139] The composition of the composite coating agent in this comparative example is NiMnCo(OH)2, Nb2O5, and ZrO2, wherein the molar ratio of the first coating element (NiMnCo), the second coating element (Nb), and the third coating element (Zr) is 1:1:0.6, the molar proportion of the coating agent is 0.19%, and the ternary precursor is Ni 0.83 Co 0.12 Mn 0.05 (OH)2, the dopants are Ti2O3, MgO, and Sc2O3, the molar ratio of the dopants is 0.6%, and the remaining steps are the same as those in Example 1, as shown in Table 1.

[0140] Table 1 is the material process records of Examples 1-10 and Comparative Examples 1-6

[0141]

[0142]

[0143]

[0144] (1) Electrochemical performance test

[0145] Preparation of positive electrode sheets: The prepared ternary positive electrode material: SP: KS-6: PVDF is dissolved in NMP in a mass ratio of 94.5%: 2%: 1.0%: 2.5%, and stirred into a paste slurry by magnetic stirring. The resulting slurry is then coated on a 15μm thick aluminum foil current collector with a coating machine and roll-formed. It is dried in an oven at 125°C and cut into positive electrode sheets of the required size.

[0146] Preparation of negative electrode sheets: Graphite: SP: CMC: SBR is dissolved in deionized water in a mass ratio of 95.5%: 1%: 1.5%: 2.0% by magnetic stirring and stirred into a paste slurry. The slurry is then coated on a 10 μm thick copper foil current collector with a coating machine and roll-formed. The mixture is dried in an oven at 115°C and cut into negative electrode sheets of the required size.

[0147] Battery assembly: Wind the positive electrode sheet, separator PP, and negative electrode sheet into the required battery cell, bake in an oven at 85℃ for 10 hours, package with aluminum plastic film, weld the tabs, and continue baking for 20 hours after the short-circuit test. After the moisture test is qualified, perform the processes of liquid injection, exhaust, sealing, pre-charging, formation, aging, etc. to obtain the required battery.

[0148] Table 2 Material capacity and cycle data test results of Examples 1 to 10 and Comparative Examples 1 to 6

[0149] project <![CDATA[Capacity / mAh·g -1 (95% SOC)]]> Cycle / times (95%SOC) Example 1 200 542 Example 2 196 560 Example 3 194 501 Example 4 201 578 Example 5 195.5 572 Example 6 197 560 Example 7 214 396 Example 8 225 359 Example 9 212 436 Example 10 196 469 Comparative Example 1 155 332 Comparative Example 2 156 307 Comparative Example 3 154 314 Comparative Example 4 155 332 Comparative Example 5 156 345 Comparative Example 6 157 362 Comparative Example 7 150 365 Comparative Example 8 154 377 Comparative Example 9 155 307 Comparative Example 10 154 316 Comparative Example 11 155 331 Comparative Example 12 155 342 Comparative Example 13 151 361 Comparative Example 14 154 373

[0150] Note: 95% SOC means that the capacity of the battery after a certain number of cycles is 95% of the initial capacity.

[0151] (2) Residual alkali test

[0152] The residual alkali content of the samples of Examples 1 to 10 and Comparative Examples 1 to 6 was tested, specifically using a potentiometric titration method. The test results are shown in Table 3:

[0153] Table 3 Test results of residual alkali and gas production data of materials in Examples 1 to 10 and Comparative Examples 1 to 6

[0154]

[0155]

[0156] It can be seen from the table that the material capacity and cycle stability obtained by the dry coating composite coating agent adopted in the present invention are improved, and the surface residual alkali is low.

[0157] Referring to the data of comparative examples 1 to 3, it can be seen that when the positive electrode material matrix is ​​not coated, the stability of the corresponding battery is significantly reduced: the capacity and cycle performance of comparative examples 1 to 3 are lower than those of embodiments 1 to 10, and the surface residual alkali and gas production rate of comparative examples 1 to 3 are higher than those of embodiments 1 to 10.

[0158] Referring to the data of comparative examples 4 to 6, it can be seen that when the positive electrode material matrix is ​​undoped, the stability of the corresponding battery is significantly reduced: the capacity and cycle performance of comparative examples 4 to 6 are lower than those of embodiments 1 to 10, and the surface residual alkali and gas production rate of comparative examples 4 to 6 are higher than those of embodiments 1 to 10.

[0159] Referring to the data of comparative examples 7 to 8, it can be seen that when the proportion of the coating elements is not within the range set in the present application, the stability of the corresponding battery is significantly reduced: the capacity and cycle performance of comparative examples 7 to 8 are lower than those of embodiments 1 to 10, and the surface residual alkali and gas production rate of comparative examples 7 to 8 are higher than those of embodiments 1 to 10.

[0160] Referring to the data of Comparative Example 9, it can be seen that when the material of the present invention is doped and the doping ratio is within the scope of the present invention, and the coating agent is not within the scope of the present invention, the stability of the corresponding battery decreases: the capacity and cycle performance of Comparative Example 9 are lower than those of Examples 1 to 10, and the surface residual alkali and gas production rate of Comparative Example 9 are higher than those of Examples 1 to 10.

[0161] Referring to the data of comparative examples 10 to 11, it can be seen that when doping and coating are within the scope of the present invention, if the molar fraction of the coating element in the positive electrode material matrix is ​​excessive, the stability of the corresponding battery will also decrease: the capacity and cycle performance of comparative examples 10 to 11 are lower than those of embodiments 1 to 10, and the surface residual alkali and gas production rate of comparative examples 10 to 11 are higher than those of embodiments 1 to 10.

[0162] Referring to the data of Comparative Example 12, it can be seen that when the material of the present invention is doped and the doping ratio is within the scope of the present invention, and the coating agent ratio is also within the scope of the present invention, if the molar fraction of the coating element contained in the lithium-containing coating element oxide is lower than the scope of the present invention, the stability of the corresponding battery will also decrease: the capacity and cycle performance of Comparative Example 12 are lower than those of Examples 1 to 10, and the surface residual alkali and gas production rate of Comparative Example 12 are higher than those of Examples 1 to 10.

[0163] Referring to the data of comparative examples 13 to 14, it can be seen that when doping and coating are within the scope of the present invention, if the molar ratio of each coating element in the lithium-containing coating element oxide is not within the scope of the present invention, the stability of the corresponding battery will also decrease: the capacity and cycle performance of comparative examples 13 to 14 are lower than those of embodiments 1 to 10, and the surface residual alkali and gas production rate of comparative examples 13 to 14 are higher than those of embodiments 1 to 10.

[0164] Based on the results of the above embodiments and comparative examples, within the range of the doping and coating materials of the present invention, if the corresponding ratios also conform to the present invention, the residual alkali and gas production rate of the positive electrode material are greatly reduced, the capacity is slightly improved, and the cycle life is also improved. Therefore, the dopant and coating agent in the present invention have the effect of reducing the amount of alkali on the surface of the material within a certain range and improving the life and capacity of the positive electrode material.

[0165] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A high nickel single crystal positive electrode material, characterized in that: It comprises a positive electrode material substrate and a coating layer prepared by a coating agent and arranged on the surface of the positive electrode material substrate; the coating agent is coated by a dry coating process; The coating agent includes a first coating agent, a second coating agent and a third coating agent; the first coating agent is a hydroxide, oxide, sulfide, nitrate or carbonate of the first coating element; the second coating agent is a hydroxide, oxide, sulfide, nitrate or carbonate of the second coating element; the third coating agent is a hydroxide, oxide, sulfide, nitrate or carbonate of the third coating element; The first coating element includes one or more of Ni, Mn, Co and B; the second coating element includes one or more of Mg, Al, Nb, W and Mo; the third coating element includes one or more of Ti, Cr, Zr, Y and Sr; The molar ratio of the first coating element, the second coating element and the third coating element is 1-15:0.1-18:0-12; The composite coating agent is coated by a dry coating process; The first coating agent is at least one of NiMnCo(OH)2, NiMnCoCO3, Co(OH)2, MnCO3, CoCO3, H3BO3, B(NO3)3, CoOOH or Mn (OH)2; The second coating agent is at least one of MgO, MgCO3, Mg(OH)2, Al2O3, Al(OH)3, MoO3, Mo(OH)3, WO3, Nb(OH)5 or Nb2O5; The third coating agent is at least one of TiO, Cr(OH)2, ZrO2, C2O5Zr, Y2O3 or Sr(OH)2; The molar fraction of the coating element in the coating layer to the positive electrode material matrix is ​​0.0001-8%; The coating layer is composed of a lithium-containing coating element oxide and a lithium-free coating element oxide; in the coating layer, the molar amount of the coating element contained in the lithium-containing coating element oxide accounts for 50% to 89% of the total amount of the coating element; In the lithium-containing coating element oxide, a molar ratio of the first coating element, the second coating element, and the third coating element is 29-100: 0-71: 0-66.

2. The high nickel single crystal positive electrode material according to claim 1, characterized in that: The structural formula of the positive electrode material matrix is ​​Li x Ni a M b N c O2, wherein 0.8≤x≤1.05, 0.8≤a≤0.98, b=1-ac, 0≤c<0.2; M is selected from at least one of Mn, Co, Al, Mg or Fe; N is a doping element selected from at least one of Ti, Ta, K, Sb, Na, B, Sc, V, Sn, Y, Zr, Mg, Cr, Nb, W or Mo.

3. A method for preparing a high-nickel single crystal positive electrode material according to any one of claims 1 to 2, characterized in that: The steps include: A) mixing a ternary precursor and lithium hydroxide monohydrate, adding a dopant, and calcining in the presence of a protective gas to obtain a calcined material; B) crushing, removing iron and sieving the calcined material to obtain a cathode material matrix; C) mixing the cathode material matrix with the coating agent, calcining again in the presence of a protective gas, and then crushing, sieving, and removing iron to obtain a high-nickel single crystal cathode material; The dopant is selected from TiO, Ti2O3, Sc2O3, MgO, K2CO3, V2O5, Cr2O3, Sb2O3, Ta2O5, Y2O3, ZrO2, Zr2O 3、 At least one of NaBO2, WO3, MoO3, and Nb2O5; the added amount of the dopant is 0.0001-0.15wt%; the molar fraction of the doping element in the positive electrode material matrix is ​​0.28-0.76%.

4. The method for preparing a high-nickel single crystal positive electrode material according to claim 3, characterized in that: Step A) The calcination is specifically carried out at 1-10°C·min -1 The heating rate is 2-4℃·min. The temperature is raised to 190-420℃ and kept at this temperature for 3.5-10.5h. -1 Raise the temperature to 690~920℃, keep warm for 8~11h; then -1 Cool down to room temperature; Step C) The calcination is specifically carried out by heating the temperature to 500-810° C. at a rate of 3-10° C. / min and keeping the temperature for 9-11 hours.

5. A lithium ion battery, characterized in that: It includes the high-nickel single crystal positive electrode material described in any one of claims 1 to 2 or the high-nickel single crystal positive electrode material prepared by the preparation method described in any one of claims 3 to 4.

Citation Information

Patent Citations

  • Method for preparing cobalt oxide coated ternary positive electrode material

    CN109713262A

  • Composite coating agent for ultrahigh-nickel single-crystal ternary positive electrode material, preparation method and application thereof

    CN112194196A

  • Anode active substance and its preparing method and anode and battery

    CN101154726A

  • Lithium battery positive-pole material, preparation method thereof and lithium-ion battery containing positive-pole material

    CN105428631A